Noninvasive evaluation of muscle mass by ultrasonography of quadriceps femoris muscle in End-Stage Renal Disease patients on hemodialysis. Issue 3 (June 2019) - Sabatino, Alice; Regolisti, Giuseppe; Delsante, Marco; Di Motta, Tommaso; Cantarelli, Chiara; Pioli, Sarah; Grassi, Giulia; Batini, Valentina; Gregorini, Mariacristina; Fiaccadori, Enrico
Summary: Background & aims: Protein-Energy Wasting (PEW) is a pathological condition of renal patients with advanced Chronic Kidney Disease characterized by a progressive reduction of energy and protein assets. Nutritional status assessment, especially for what concerns muscle mass, is essential for both the identification of patients at risk for the development of PEW, as well as monitoring the effects of nutritional interventions. Ultrasound methods are easily applicable at the bedside for quantitative assessment of skeletal muscle. The present study was aimed at evaluating quadriceps rectus femoris thickness (QRFT) and quadriceps vastus intermedius thickness (QVIT) in patients on chronic hemodialysis. Methods: This was a prospective observational study. Three groups of adult patients were studied: young healthy subjects, well-nourished hospitalized patients with normal renal function, and End-Stage Renal Disease patients on hemodialysis (ESRD-HD). QRFT and QVIT were measured at two sites bilaterally (8 measures/patient) and were compared between groups, and also between subgroups of ESRD-HD patients stratified on the basis of conventional nutritional status parameters. Results: We enrolled 35 healthy subjects, 30 hospitalized patients, and 121 ESRD-HD patients on hemodialysis. QRFT and QVIT of ESRD patients on hemodialysis were lower than those of both control groups ( P < 0.001). After stratifying ESRD patients into subgroups based on nutritional variable cut-offs commonly used to define PEW in this clinical setting (BMI [≥ 23 vs <23 kg/m 2 ], albumin [≥3.8 vs <3.8 g/dL]) and malnutrition inflammation score (MIS) status (<6 vs ≥6), QRFT and QVIT of patients with worse nutritional status were significantly lower than those of well-nourished ESRD-HD patients ( P value range: <0.001 to <0.05). Conclusion: Skeletal muscle ultrasound is a simple and easily applicable bedside technique in the dialysis units, and could represent an adequate tool for the identification of patients with reduced muscle mass.